Abacus computing tool – from history to application in mathematical education - Sanja M. Maričić; Bojan D. Lazić (Inovacije u Nastavi, 2020)
Bearing in mind that the history of mathematics and its discoveries can play a significant role in mathematics education today, the authors draw attention to an ancient computing tool – abacus, and point out its role, importance, values, and opportunities it offers in working with children. In order to achieve this goal and using the method of theoretical analysis, the authors researched the values of application of the Japanese abacus (soroban) in mathematics education through the following aspects: learning mental arithmetic, understanding the place value of a digit, contribution to working with children with developmental disabilities, primarily with visual and hearing impairments, as well as contributions to children’s mental development and problem-solving abilities. Based on numerous research papers and views, the authors conclude that Japanese abacus can have many benefits in working with children in mathematics education, among which the most important are conceptual understanding of mental arithmetic and developing mental computation and problem-solving skills, gaining a clear mental picture of the structure of numbers, their magnitude and relationship, understanding the place value of a digit, but also developing motivation and positive attitudes toward mathematics.